Strategic Implementation of Corporate Identity in A Design Company - Sofiana, Yunida (Humaniora, 2013)
Implementation of Corporate Identity has been increase enormously over the past 20 years and predicting will be increase higher in the future. Design Company will be the one who will get the big impact from these changes. Business world believes that corporate identity as important aspect to consider if they want to succeed and competed in their business. An important part of this article is to learn about corporate identity from the literatures and then apply that knowledge and the experiences gained to discuss the strategic implementation of a corporate identity within Design Company. Many companies especially design companies try very hard and seriously to develop a corporate identity of their clients other than their own. As part of the review, the concept of corporate identity, corporate image, corporate communication, corporate structure, corporate culture and how design companies implement and designing a corporate identity for themselves will be examined.